Proceedings of the Thirtieth Annual ACM-SIAM Symposium on Discrete Algorithms 2019
DOI: 10.1137/1.9781611975482.167
|View full text |Cite
|
Sign up to set email alerts
|

Full Tilt: Universal Constructors for General Shapes with Uniform External Forces

Abstract: We investigate the problem of assembling general shapes and patterns in a model in which particles move based on uniform external forces until they encounter an obstacle. In this model, corresponding particles may bond when adjacent with one another. Succinctly, this model considers a 2D grid of "open" and "blocked" spaces, along with a set of slidable polyominoes placed at open locations on the board. The board may be tilted in any of the 4 cardinal directions, causing all slidable polyominoes to move maximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
(32 reference statements)
0
27
0
Order By: Relevance
“…Recent work strengthened these results and showed PSPACE-Completeness for all three problems even when only allowing 1 × 1 pieces [2]. Additional work has focused on the application of the tilt model for the assembly of general shapes [8], [10], [11], including universal constructors [1], [2], and sorting polyominoes [9].…”
Section: Previous Workmentioning
confidence: 89%
See 2 more Smart Citations
“…Recent work strengthened these results and showed PSPACE-Completeness for all three problems even when only allowing 1 × 1 pieces [2]. Additional work has focused on the application of the tilt model for the assembly of general shapes [8], [10], [11], including universal constructors [1], [2], and sorting polyominoes [9].…”
Section: Previous Workmentioning
confidence: 89%
“…Later work in Ref. [1] relaxed the constraint on tile size and showed the Relocation and Reconfiguration Problems were PSPACE-Complete when only a single 2 × 2 polyomino is allowed. Recent work strengthened these results and showed PSPACE-Completeness for all three problems even when only allowing 1 × 1 pieces [2].…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Given a shape in their buildable class, a tilt model configuration could be generated to assemble that shape through a sequence of tilts. This drop-shape construction work was extended in [3]. Rather than focusing on designing configurations for specific drop-shapes, the authors create a general drop-shape constructor.…”
Section: Classmentioning
confidence: 99%
“…The authors also showed that a dualrail logic fanout was not possible with only 1×1 tiles, which seemed to serve as evidence that this problem was not PSPACE-complete. Following, in [3] the authors proved that the occupancy problem is PSPACE-complete if a single "large" polyomino is allowed (they used a single 2 × 2 polyomino along with 1 × 1 tiles).…”
Section: Classmentioning
confidence: 99%